2016
DOI: 10.1073/pnas.1517520113
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into photoactivation of an adenylate cyclase from a photosynthetic cyanobacterium

Abstract: Cyclic-AMP is one of the most important second messengers, regulating many crucial cellular events in both prokaryotes and eukaryotes, and precise spatial and temporal control of cAMP levels by light shows great promise as a simple means of manipulating and studying numerous cell pathways and processes. The photoactivated adenylate cyclase (PAC) from the photosynthetic cyanobacterium Oscillatoria acuminata (OaPAC) is a small homodimer eminently suitable for this task, requiring only a simple flavin chromophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 34 publications
10
106
0
Order By: Relevance
“…The conserved Tyr-125 of OaPAC, at the junction between the α3 helix and the AC domains, forms an intersubunit hydrogen bond with Asn-256B (8). OaPAC(Y125F) and OaPAC(Y125C) show no activity, yet OaPAC(Y125S) behaves normally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The conserved Tyr-125 of OaPAC, at the junction between the α3 helix and the AC domains, forms an intersubunit hydrogen bond with Asn-256B (8). OaPAC(Y125F) and OaPAC(Y125C) show no activity, yet OaPAC(Y125S) behaves normally.…”
Section: Discussionmentioning
confidence: 99%
“…This change leads to different downstream effects in different proteins; for example in BlrP1, it affects the coordination of essential metal ions at the active site of the neighboring domain (7). The BLUF domain of OaPAC (residues 1-100) shows similarities to BlrP1, but the mechanism of signal transmission to the active site must be entirely different because it involves mutual interactions of the two BLUF domains (8). The crystal structure of OaPAC in the dark state (PDB 4YUS) revealed that the BLUF domains sit at one end of a coiled coil (residues 103-125), with the AC domains at the other end (residues 126-350).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations